High‐Resolution Characterization of a Chlorinated Solvent Impacted Aquifer Using a Passive Profiler. Issue 4 (3rd October 2020) - Schneider, Haley A.; Jackson, W. Andrew; Hatzinger, Paul B.; Schaefer, Charles E.
Abstract: A direct‐drive high‐resolution passive profiler (HRPP) was developed to quantify and delineate concentrations of chlorinated volatile organic compounds (CVOCs), geochemical indicators and CVOC‐degrading microorganisms/genes, as well as to perform compound‐specific stable isotope analysis (CSIA) of CVOCs and estimate interstitial velocity at <30‐cm resolution. The profilers can be coupled together to provide a continuous sample interval and advanced to depths up to approximately 9 m below‐ground surface (bgs) within saturated media where direct‐push techniques are feasible. The HRPP was field tested in a previous dense nonaqueous phase liquid (DNAPL) source zone at the former Naval Air Station in Alameda, CA. HRPP data sets were compared to the following traditional groundwater data sets: CVOC and anion concentrations in standard and multilevel monitoring well water samples, CVOC concentrations in soil core samples, qualitative contaminant profiles delineated with a membrane interface probe (MIP), microbial community and CSIA profiles from Bio‐Traps® deployed in wells, groundwater velocity from passive flux meters (PFMs), lithologic profiles correlated with MIP electrical conductivity (EC), and velocity estimates based on permeability profiles measured with a Geoprobe hydraulic profiling tool (HPT). In some cases, the HRPP data were equivalent to traditional techniques and, in other cases, the HRPP data were more representative of local variability rather than bulk aquifer conditions. Overall the results support the use of the HRPP to provide high‐resolution data on concentrations, velocity, and microbial activity in temporary direct‐push deployments without well installation, providing a new tool to better assess source zones and contaminated groundwater plumes, even in low permeability media, and to increase the fidelity of site transport models.